Mergers and Acquisitions in India’s Public Sector Banks: Causes, Effects, and Performance Implications - Chinnakaran, Anand; Maharajan, Jeseena (Journal of Global Economy, Business and Finance, 2026)
Mergers and Acquisitions (M&A) in Indian Public Sector Banks (PSBs) have had a significant contribution in restructuring the banking sector. Consolidations aim to enhance financial stability, improve operational efficiency, and boost global competitiveness. This study investigates the driving factors behind these consolidations and their economic and operational consequences. Using case studies of prominent mergers, such as Punjab National Bank (PNB) with Oriental Bank of Commerce (OBC) and United Bank of India (UBI), and Bank of Baroda (BoB) with Vijaya Bank and Dena Bank, the study examines post - merger financial performance. A mixed - method research approach is adopted, combining financial ratio analysis, statistical hypothesis testing, and qualitative surveys. Findings suggest that while M&As enhance capital strength and efficiency, they pose short - term operational challenges. The study concludes that sustained technological investment and workforce training are critical for long - term success.